Group of teenage girls eating lunch at a picnic table - Unknown:::Creator::::::::::::
Negative shows a group of teenage girls eating at a picnic table in a wooded area which may be at Alum Rock Park in San Jose, California. This is possibly a picture of members of the YWCA's Contenta Hora group. Contenta Hora was a YWCA club for Latinas.